2022
DOI: 10.1002/ijc.34201
|View full text |Cite
|
Sign up to set email alerts
|

Combined identification of three lncRNAs in serum as effective diagnostic and prognostic biomarkers for hepatitis B virus‐related hepatocellular carcinoma

Abstract: Hepatitis B virus‐related hepatocellular carcinoma (HBV‐related HCC) is a common, highly invasive malignant tumor associated with a high mortality rate. This study aimed to identify the effective diagnostic and prognostic biomarkers for HBV‐related HCC. With HBV‐related HCC RNA‐sequencing data of The Cancer Genome Atlas (TCGA) database, 159 differentially expressed long noncoding RNAs (lncRNAs) between HBV‐related HCC and para‐carcinoma normal samples were identified, and 12 lncRNAs were eventually assessed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In terms of clinical diagnosis, a single tumor biomarker has some limitations owing to the complicated pathological alterations associated with the onset and progression of cancer. 37 Thus, to reduce the drawbacks of the low sensitivity and specificity of a single lncRNA for diagnosis, we further explored the diagnostic value of the combination of ADAMTSL4-AS1, AC067931, SOCS2-AS1 with AFP. This combination of the 3 lncRNAs with AFP could distinguish between patients with HCC and those with other benign liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical diagnosis, a single tumor biomarker has some limitations owing to the complicated pathological alterations associated with the onset and progression of cancer. 37 Thus, to reduce the drawbacks of the low sensitivity and specificity of a single lncRNA for diagnosis, we further explored the diagnostic value of the combination of ADAMTSL4-AS1, AC067931, SOCS2-AS1 with AFP. This combination of the 3 lncRNAs with AFP could distinguish between patients with HCC and those with other benign liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identifies 11 cuproptosis-related lncRNAs, constructs their prognosis-related signatures, and finds AC234031.1, AC011921.1, AC005332.5, RNF32-AS1 and CKMT2-AS1 are high-risk lncRNAs, while TNFRSF14-AS1, AL031275.1, NINJ2-AS1, EMX2OS, AC092140.2, and AC015922.3 are low-risk lncRNAs. Relevant studies have shown that the lncRNA signature of AC005332.5 is a potential diagnostic biomarker for HBV-related hepatocellular carcinoma (HCC) patients ( Fu et al, 2022 ), the lncRNA signature of CKMT2-AS1 is closely related to the prevention of colorectal cancer ( Zhuang et al, 2022 ), the lncRNA signature of TNFRSF14−AS1 can be used as a prognosis marker for bladder cancer ( Wang et al, 2021a ), the lncRNA signature of AC015922.3 is a novel biomarker for esophageal squamous cell carcinoma ( Liu et al, 2020 ), and downregulation of lncRNA EMX2OS can independently predict shorter recurrence-free survival in classical papillary thyroid cancer ( Gu et al, 2018 ). However, this study first investigated the prognosis profile of NINJ2-AS1, RNF32-AS1, AC234031.1, AC011921.1, AC092140.2, and AL031275.1.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of AC005332.5, ELF3-AS1, and LINC00665 were considerably altered with different tumor stages or grades. According to a survival study, the factors AC005332.5, ELF3-AS1, and LINC00665 strongly correlated with overall survival outlook (Fu et al, 2022). Ahluwalia et al discovered LINC00665 earlier this year to act as a mechanistic tool for HBsAg to induce hepatocarcinogenesis.…”
Section: Lncrnas Involved In Hcc Diagnosis and Prognosismentioning
confidence: 99%